Instrumenty zapewnienia właściwej podaży dóbr publicznych – przegląd wybranych zagadnień na przykładzie ochrony przyrody w lasach - Kaliszewski, Adam (Leśne Prace Badawcze, 2011)
The four main categories of measures taken by the state for the provision of public goods are illustrated using the example of forest conservation. These categories are: legal regulations, direct provision by the government, subsidies and fiscal policy, and an institutional framework for creating markets for public goods. Numerous practical examples are given for each category. The article concludes that optimal forest conservation policy needs to be based on a mix of different instruments and institutional arrangements.